PENGAJARAN MATEMATIKA PADA ANAK USIA DINI (Martabat: Jurnal Perempuan dan Anak, 2017)
Mathematics presents in all of life, so everyone needs to have basic math skills, including early childhood. Understanding and perception of the right of children about mathematics will give good impact on a child's cognitive development. So, the teachers and parents need a good understanding of mathematics.  It can be able to provide teaching mathematics ideal for children. Teaching mathematics at that age should take into account the range of material and the correct method. The method can be used in teaching mathematics to children aged are playing while learning and practice. The media used should be a real object and pictograf. The material that can be taught include: numbers, algebra, measurement, geometry and data collection. Key words: mathemathic, young learner